2017
DOI: 10.7322/abcshs.v42i3.932
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for intestinal parasite infections in schoolchildren, in the city of Santarém, Pará State, Brazil

Abstract: Introduction: Intestinal parasites are common in children in poor countries around the world, and are the cause of serious health problems. Objective: To evaluate the prevalence of intestinal parasites in schoolchildren in Santarém, and associated socio-environmental risk factors. Methods: Questionnaires were applied to parents, and fecal exams were performed by direct method and sedimentation. Results: The parasites that prevailed were Entamoeba coli (20.4%) and Ascaris lumbricoides (9.0%). The family income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
4
2
4
Order By: Relevance
“…A study from Rio de Janeiro, Brazil, reported statistical differences between the prevalence of Blastocystis in men and women, and proposed that economic activities could explain this finding [ 2 ]. Contrary to these results, we did not find any statistical association between Blastocystis subtypes and sex, despite many adult women working in the household in our study population, which could increase the risk of infection due to food contamination [ 45 , 48 ], lack of sanitation [ 2 ], and domestic animal handling in periurban communities of Arequipa [ 39 ]. On the other hand, age is another important demographic factor associated with infection and plays a key role in intestinal infections, as described in other studies [ 5 , 42 , 49 ].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…A study from Rio de Janeiro, Brazil, reported statistical differences between the prevalence of Blastocystis in men and women, and proposed that economic activities could explain this finding [ 2 ]. Contrary to these results, we did not find any statistical association between Blastocystis subtypes and sex, despite many adult women working in the household in our study population, which could increase the risk of infection due to food contamination [ 45 , 48 ], lack of sanitation [ 2 ], and domestic animal handling in periurban communities of Arequipa [ 39 ]. On the other hand, age is another important demographic factor associated with infection and plays a key role in intestinal infections, as described in other studies [ 5 , 42 , 49 ].…”
Section: Discussioncontrasting
confidence: 95%
“…However, in rural areas, socioeconomic status and food or water contamination are associated with exposure to livestock and wildlife, which could explain the reported distribution of specific subtypes in rural communities of Turkey [ 42 ]. General prevalence studies on intestinal parasite infections have been associated with the presence of Blastocystis infection and untreated water consumption, feces disposal practices, and inadequate hand-washing habits [ 21 , 45 ]. There is little literature available related to how dietary practices influence the presence of Blastocystis in the human gut.…”
Section: Discussionmentioning
confidence: 99%
“…According to demographic variables, the scientific literature reports statistical differences between men and women mainly for the economic activities (18). Contrary to these results, we have not found statistical association between Blastocystis subtypes and sex, in spite of many adult woman are dedicated to welfare home in the study sample and considering this activity as risk of infection due to food contamination (45,46), lack of sanitation (18) and raising animals in periurban communities from Arequipa (36). By the other hand, age is another important demographic factor of exposition and play a key role in intestinal infections as referred in other studies (13,39,47).…”
Section: Discussioncontrasting
confidence: 94%
“…However in rural places, socioeconomic position, food and water combined to raising animals is the reason of specific subtypes distribution in rural communities (39). General prevalence studies on intestinal parasite infections has associated the presence of Blastocystis infection to untreated water consumption, final feces disposal and inadequate hands washing habits (21,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation